Experimental Investigation of the Effect of Brake Disconnished by Hvof Method - Salih Karanfi̇l; Faruk Emre Aysal; Mehmet Çakmakkaya; Hüseyin Bayrakçeken; Mustafa Babagi̇ray (International Journal of Automotive Science and Technology, 2019)
In this study; brake discs used in vehicles have investigated. The behavior of these discs during braking, wear and braking distance performance of the coated and uncoated surfaces during the braking process were evaluated. The surface of the commercially produced discs was coated with a thickness of 1 mm using the HVOF (High Velocity Oxy-Fuel) coating method. In the coating process CoNiCrAlY, WC-Co (88/12), NiCrBSi and MoNiCrBSiFe (Mo 25%) 4 (four) different ceramic powders were used respectively. Wear and brake distance tests of coated and uncoated discs were performed by braking in a total of 20 brakes in 15 seconds on the brake-suspension tester.